Prohibición del cambio de domicilio fiscal y derecho de defensa del deudor tributario en el procedimiento de cobranza coactiva - Bueno Floriano, Teresita Marcelina (2017)
This thesis clearly denotes multiple arbitrariness to which citizens are exposed, as taxpayers, who maintain tax debts before the Tax Administration, having initiated a corresponding collection procedure coercive, prohibits that said taxpayer can change their address fiscal. The damage and the affectation to the constitutional right of defense was denoted that said prohibition of change of fiscal domicile generates in the legal-procedural sphere of the tax debtor. This research work has been based on the Tax Power, which not only implies the existence of an all-embracing power under which the State, in its purpose of collection, but which must be respected and compatible with the Political Constitution of the Peru, specifically with the fundamental rights of the administered; Which must be governed by the permanent guidelines of the Administration's actions. Thus, in compliance with the constitutional right of defense of all tax debtors, the Tax Administration must allow the tax domicile to be set and changed in the procedures that the tax debtors maintain in their jurisdiction, in order to protect the fundamental rights of the administration; Especially the right of defense, it is recommended to amend the second paragraph of Article 11 of the Tax Code, eliminating the current prohibition to change the tax domicile in a coercive collection procedure